2020
DOI: 10.1186/s12931-020-01409-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity to metal and silica associates with sarcoidosis in Dutch patients

Abstract: Background: Involvement of metals or silica in the pathogenesis of sarcoidosis has been suggested by several case reports and specific epidemiological studies. However, the combination of occupational exposure and an immunological reaction has not been studied before in a group of sarcoidosis patients and non-sarcoidosis controls. Methods: In 256 sarcoidosis patients and 73 control patients with obstructive sleep apnea, exposure to metal and silica was assessed using a questionnaire consisting of a complete oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…It seems plausible to assume that this will also be the case for other inorganic triggers. In a previous paper, we showed that occupational exposure to metal/silica determined by a job exposure matrix (JEM) is not predictive for a positive LPT [19]. A possible explanation may be that the JEMs are designed to be very specific, and will not capture individuals experiencing coincidental high-risk exposure while carrying out low-risk jobs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It seems plausible to assume that this will also be the case for other inorganic triggers. In a previous paper, we showed that occupational exposure to metal/silica determined by a job exposure matrix (JEM) is not predictive for a positive LPT [19]. A possible explanation may be that the JEMs are designed to be very specific, and will not capture individuals experiencing coincidental high-risk exposure while carrying out low-risk jobs.…”
Section: Discussionmentioning
confidence: 98%
“…*P-value of any positive LPT SI > 2•0 was calculated using Pearson's χ 2 test; the other P-values were calculated using Fisher's exact test. The two silica-positive patients were also included in a previous study [19]. ELISPOT = enzyme-linked immunospot.…”
Section: Inorganic Antigensmentioning
confidence: 99%
“…A difference is that the number of lymphocytes used per test is higher for MELISA (> 1 Â 10 6 cells) than for the conventional LPT (100,000-250,000), a difference that is believed to increase the sensitivity of the MELISA LPT. 37,38 In the analysis by Beijer et al, 37 patients with sarcoidosis in an interstitial lung disease outpatient clinic in The Netherlands were invited to participate in the study. To assess occupational exposures to silica and metals, a JEM was developed for each patient.…”
Section: Metal Dustsmentioning
confidence: 99%
“…Silica exposure has been associated with sarcoidosis or sarcoid-like granulomatous lung disease (8)(9)(10)(11)(12)(13). Epidemiological studies have noted a high incidence of sarcoidosis in patients with silica exposure (10,11).…”
Section: A B C D Ementioning
confidence: 99%
“…Inhalation of beryllium can cause granulomatous lung disease that mimics sarcoidosis (7), and other metals and inorganic dust have also been associated with a granulomatous response (4)(5)(6). Silica might be a trigger for sarcoidlike granulomatous lung disease, and several studies have reported the association between silica exposure and sarcoidosis or sarcoid-like granulomatous lung diseases (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%